Mapping the Reproductive Support Capacity of Beef Cattle as an Effort to Intensify Rearing in the Baluran National Park Area - Achadiah Rachmawati; Rositawati Indrati; Anie Eka Kusumasti; Mas Ayu Ambayoen; Siti Azizah; Leni Sri Pangesti (Jurnal Ilmu-Ilmu Peternakan, 2023)
Since the 1960s, or for four generations, farmers who live close to Baluran National Park have been grazing or raising beef cattle extensively illegally. Since there is not enough forage for beef cattle, their presence in the Baluran National Park area interferes with the preservation of wildlife. This is brought on by the shortage of forage. Farmers continue to use the traditional rearing method, which was self-taught and is not supported by systematic recording. As a result, there is a high risk of inbreeding, difficult calving, and disease contracting, particularly in cases of cattle collapses and outbreaks of FMD in even hoofed animals like cows. The absence of livestock extension staff in the region contributes to farmers' lack of understanding about reproduction, particularly estrus detection and illness prevention. The Animal Husbandry and Fisheries Service, Situbondo Regency, and the Community and Livestock Research Group (CLRG) Team of the Faculty of Animal Science, Universitas Brawijaya, Malang, have worked together to aid in the form of Indigofera sp. seeds as forage for animal feed, forage processing technology into silage, the concept of communal pens (groups) for farmers, and facilitate the formation of the Lembu Brawijaya. Direct observation of beef cattle and interviews with farmers and Baluran National Park personnel will be the research methods employed in the project. The outcomes of this study can serve as a guide for figuring out the best course of action for increasing livestock productivity and intensive rearing. It is also expected that cattle will not grazed in the Baluran National Park area and restore its function as a biosphere conservation area.  Farmers can monitor their cattle better when they raise them intensively, which is supported by systematic recording and disease prevention.